Cost‐effectiveness of CBT, SSRI, and CBT+SSRI in the treatment for panic disorder. (3rd July 2013) - van, F. J.; Stant, A. D.; van, W. J. P. J.; Mersch, P. P. A.; den Boer, J. A.
<x xml:space="preserve">Abstract</x> Objective The objective of this study was to assess the cost‐effectiveness of three empirically supported treatments for panic disorder with or without agoraphobia: cognitive behavioral therapy (CBT), pharmacotherapy using a selective serotonin reuptake inhibitor (SSRI), or the combination of both (CBT+SSRI). Method Cost‐effectiveness was examined based on the data from a multicenter randomized controlled trial. The Hamilton Anxiety Rating Scale was selected as a primary health outcome measure. Data on costs from a societal perspective (i.e., direct medical, direct non‐medical, and indirect non‐medical costs) were collected in the study sample (N = 150) throughout a 24‐month period in which patients received active treatment during the first twelve months and were seen twice for follow‐up in the next twelve months. Results Total costs were largely influenced by costs of the interventions and productivity losses. The mean total societal costs were lower for CBT as compared to SSRI and CBT+SSRI. Costs of medication use were substantial for both SSRI and CBT+SSRI. When examining the balance between costs and health outcomes, both CBT and CBT+SSRI led to more positive outcomes than SSRI. Conclusion Cognitive behavioral therapy is associated with the lowest societal costs. Cognitive behavioral therapy and CBT+SSRI are more cost‐effective treatments for panic disorder with or without agoraphobia as compared to SSRI only.